2008
DOI: 10.2174/092986608786071193
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Cleavage of Bid and Procaspase-7 by Caspase-2 at Lower pH

Abstract: The activity of caspase-2 was examined under varying biochemical conditions with the synthetic and protein substrates, Bid and procaspase-7. The results indicate that it was largely influenced by pH which might be one reason behind the inconsistency for the cleavage of its established substrates during caspase-2-induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Subsequent reports confirmed this finding using purified caspase-2 [131,150,151]. It was recently reported that four times more caspase-2 (in its preferred pH 6.75 buffer) than caspase-8 was required to cleave purified Bid [145]. This finding was consistent with less quantitative prior data implying that Bid cleavage by caspase-8 was more efficient than by caspase-2 [131,[149][150][151].…”
Section: Protein Substratessupporting
confidence: 64%
See 2 more Smart Citations
“…Subsequent reports confirmed this finding using purified caspase-2 [131,150,151]. It was recently reported that four times more caspase-2 (in its preferred pH 6.75 buffer) than caspase-8 was required to cleave purified Bid [145]. This finding was consistent with less quantitative prior data implying that Bid cleavage by caspase-8 was more efficient than by caspase-2 [131,[149][150][151].…”
Section: Protein Substratessupporting
confidence: 64%
“…Cleavage efficiencies have only been published for two substrates (Table 2). In vitro, caspase-2 was recently determined to exhibit maximal activity against protein substrates in low pH buffers (5.5-7.0) lacking salt [145]. Interestingly, peptide substrates were most efficiently cleaved in neutral or only slightly basic buffers [145,146].…”
Section: Substrates and Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage of human Mdm2 by caspase-2 has been reported to stabilize p53 and might contribute to the increased p53-dependent drug resistance of non-small cell lung carcinoma cell lines (27). Caspase-2 does not cleave (30) or proteolytically activate executioner caspases (31), with the exception of cleaving caspase-7 at pH 2.0, which is most likely not relevant in vivo (32).…”
mentioning
confidence: 99%
“…28 Hence, to exclude the possibility that the presence of active recombinant caspase-2 may lead to the activation of downstream effector caspases that could cleave additional proteins in the cell lysates, we examined the processing of caspase-3 and -7, as well as the activities of these caspases in recombinant caspase-2-treated cytosol fractions. Western blot analysis of these lysates revealed processing of endogenous caspase-2, whereas processing of endogenous caspase-3 or -7 was not detected (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%